A study of intracoronary thrombolytic agents in high thrombus burden lesions during primary PCI - Venkata RS. Subrahmanya Sarma; K. Gopalakrishna; K. Purnachandra Rao; G. Somasekahr; P.S.S. Chowdary; P. Raghuram; B. Dasarath; Manohar Reddy; Ramkishore; Raji Veeramachineni; Y. Sasidhar; M. Prasad (Indian Heart Journal)
Objectives: High thrombus burden during Primary Percutaneous Coronary Intervention begets poor outcomes; there are several lacunas in the management of those patients.- The purpose of this study is to analyse the long-term outcomes of patients undergoing primary percutaneous coronary intervention with high thrombus burden, treated with intracoronary thrombolysis as an adjunctive therapy. Methods: In this prospective observational study, 108 consecutive primary percutaneous coronary intervention patients with high thrombus burden were stratified into two groups basing on whether they received intracoronary thrombolytic agent before stent implantation. The primary outcome is Net Adverse Clinical Events. Secondary outcomes include Major Adverse Cardiac Events, and all other individual components of the Net Adverse Clinical Events when analysed separately. Results: The primary outcome events occurred in 21 patients (26 %) in the Primary stent group (n = 80), whereas it occurred in 2 patients (6 %) in the primary intra-coronary thrombolysis group (n = 28), this study shows that there is no difference in primary endpoints in both groups (26 % Vs 7 %, p-value – .042, Hazard ratio - 2.56; 95 % CI - .76–8.57), however Kaplan–Meier event-free survival curves show that both the curves are well separated apart even at the end of the one year of follow – up. Conclusion: There is no difference in the primary outcome events in both groups, however there was a consistent increase in events in the primary stent group over the one-year follow-up period. These findings suggest the need for a larger randomized clinical trial to confirm and further elucidate these results.